6.4k views
1 vote
I need the ans asap pls

I need the ans asap pls-example-1
User Hernan
by
4.6k points

1 Answer

1 vote

Answer:


\bf\implies \: 18y \: - 12

Explanation:


\bf \implies15(y - 4) - 2(y - 9) + 5(y + 6)
\bf \implies \: (15 * y )+ (15 * - 4 )- (2 * y )+ ( - 2 * - 9) + (5 * y )+ (5 * 6)
\bf \implies (15y) + ( - 60) - (2y) + (18) + (5y) + (30)
\bf \implies 15y - 60 - 2y + 18 + 5y + 30
\bf \implies (15y - 2y + 5y) - (60 + 18 + 30)
\bf \implies 18y - 12 \: \underline{ \red{Ans.}}

User Sunny Agarwal
by
4.4k points